The Effect of the First Goal on the Score of the Match and Home Advantage in Football: Analysis of Turkish Super League and 1st League in Pre-Pandemic and Pandemic Period - Serdar Yıldırım; Gökhan Hadi; Kemal Göral (Türk Spor ve Egzersiz Dergisi)
The present study was conducted to examine and analyze the home advantage in the Turkish Soccer Super League and TFF 1st Soccer League matches played pre-pandemic and pandemic periods. The study data that were obtained by evaluating the results of the competitions played in the last two seasons (2019-2020 and 2020-2021) were analyzed by using the number of matches won by the teams as the home and away teams, the effects of the first goal scored on the score of the match, and the home advantage. The data obtained in this way were recorded in the SPSS 18.0 programme, was then interpreted by calculating the frequency and percentage values. In the last two seasons that were examined, as the pre-pandemic period, the home advantage was found to be 53.57% in a total of 486 matches in the Super League and TFF 1st League in the 2019-2020 season, and the home advantage value was 52.42% in the Super league, and 54.37% in the TFF1 League. In the 2020-2021 season, which has been continued during the pandemic process, the percentage of total home advantage in 420 matches in the Super League and 306 matches in the TFF 1st League was found to be 50.64%, and the percentage of home advantage values decreased to 50.79% in the Super League and 50.43% TFF 1st Soccer League. Pre pandemic period, after the first goal scored by the home teams in the competitions in the 2019-2020 season, 61.11% of the matches in the TFF 1st League, and 72.97% in the Super League ended with a win; and in the 2020-2021 season of the pandemic period, 74.52% of the matches ended with a win in the Super League, and 77.85% of them resulted in a win in the TFF 1st League. As a result, the rate of leaving the football pitch with a win after the first goal in the matches played in both the Super League and the 1st League was found to be quite high. Based on this viewpoint, it can be argued that the first goal scored in football competitions is an important factor affecting the result directly. However, it is considered that the spectator factor plays an important role in the home advantage in football based on the fact that the home advantage values of the football teams decreased in the season played with spectators compared to the values in the games played in the season without spectators.